Visualization Tool for Pathfinding Algorithms - Mathias Sam, Francis (Universiti Malaysia Sarawak, (UNIMAS), 2023)
This final year project aims to address the challenges faced by students in comprehending pathfinding algorithms by developing a web-based visualization tool. The tool's primary objective is to provide students with a visual representation of algorithmic processes, enabling them to grasp the underlying concepts more effectively. By incorporating interactive features and step-by-step animations of popular pathfinding algorithms, the tool empowers students to actively engage in the learning process and experiment with different algorithmic approaches. Furthermore, the tool serves as a valuable resource for educators, facilitating the teaching of pathfinding algorithms in a more engaging and interactive manner. With its user-friendly interface and emphasis on visualization, the proposed tool has the potential to enhance students' understanding, problem-solving skills, and overall proficiency in algorithmic thinking. Ultimately, the successful development of this web-based visualization tool can contribute to bridging the gap between theory and practice, enabling students to navigate the complexities of pathfinding algorithms with greater ease and confidence.